Effectiveness of Applying the Sorogan and Bandongan Methods in Learning the Yellow Book in PP. Darul Qur'an, Mojokerto City - Islachiyatul Asyrofiyah; Rustam Ibrahim; Siti Choiriyah (al-Afkar, Journal For Islamic Studies, 2024)
The effectiveness of applying the sorogan and bandongan methods is one that is quite difficult to apply to santri with awareness, it is better for the santri to first study using these two methods before taking further education at the Islamic boarding school, because basically it is the santri who have mastered these two methods who can learn The benefits of being able to read and understand books in Islamic boarding schools. It is common that using the two methods above will result in various obstacles, starting from less effective teaching time, maximum patience, diligence, perseverance, tenacity and personal discipline of a kyai (ustadz). The aim of the research is to find out and develop the effectiveness of the sorogan and bandongan methods in learning the yellow book in Islamic boarding schools so that students can understand and read the yellow book in accordance with the science of nahwu and shorof. The method used in this research is descriptive qualitative, the research subjects consist of Islamic boarding school administrators, ustadz and Islamic boarding school students, while the data collection methods are interviews, observation and documentation. The data analysis used in the research is domain analysis, verification data display and conclusions. Based on the results of data analysis in this discussion, it can be seen that the sorogan and bandongan methods are one of the factors that play an important role in the success of the ability to read and understand the yellow book at the Tahfidz Putri Darul Quran Islamic Boarding School, Mojokerto City. The effective use of these methods varies, starting from giving assignments, holding sorogan, and practices as well as questions and answers and discussions when performing syawir or murojaah, as well as holding learning evaluations.